The effectiveness of matrix cauterization with trichloroacetic acid in the treatment of ingrown toenails - Erdinc Terzi; Ulas Guvenc; Belma Türsen; Tamer İrfan Kaya; Teoman Erdem; Ümit Türsen (Wolters Kluwer Medknow Publications, 2015)
Ingrown toenail is an often painful clinical condition that usually affects the big toe. Chemical matricectomy with phenol has a low recurrence rate and good cosmetic results. However, it produces extensive tissue destruction that can result in drainage and delayed healing. Alternatives such as sodium hydroxide and trichloroacetic acid (TCA) have therefore come into vogue. A total of 39 patients with 56 ingrown toenail edges underwent chemical matricectomy with 90% TCA after partial nail avulsion. In most of the patients, adverse effects such as postoperative pain and drainage were minimal. One patient who underwent matricectomy had recurrence in a single nail edge (1.8%) at 12 months follow-up. No recurrence was observed among 38 patients during the mean follow-up period. This was considered to be statistically significant (P < 0.001). Partial nail avulsion followed by TCA matricectomy is a safe, simple, and effective method with low rates of postoperative morbidity and high rates of success.